Estrogen Receptor-Targeted Contrast Agents for Molecular Magnetic Resonance Imaging of Breast Cancer Hormonal Status - Pais, Adi; Degani, Hadassa (Frontiers in Oncology, 2016)
The estrogen receptor α (ER) is over expressed in most breast cancers and its level serves as a major prognostic factor. It is important to develop quantitative molecular imaging methods that specifically detect ER in vivo and assess its function throughout the entire primary breast cancer, as well as in metastatic breast cancer lesions. This study presents the biochemical and molecular features, as well as the magnetic resonance imaging effects of two novel ER- targeted contrast agents (CAs) based on pyridine-tetra-acetate-Gd(III) chelate conjugated to 17β-estradiol (EPTA-Gd) or to tamoxifen (TPTA-Gd). The experiments were conducted in solution, in human breast cancer cells and in severe combined immunodeficient mice implanted with transfected ER-positive and ER-negative MDA-MB-231 human breast cancer xenografts. Binding studies with ER in solution and in human breast cancer cells indicated affinities in the micromolar range of both CAs. Biochemical and molecular studies in breast cancer cell cultures showed that both CAs exhibit estrogen like agonistic activity, enhancing cell proliferation, as well as up-regulating cMyc oncogene and down-regulating ER expression levels. The MRI longitudinal relaxivity was significantly augmented by EPTA-Gd in ER-positive cells as compared to ER-negative cells. Dynamic contrast enhanced studies with EPTA-Gd in vivo indicated specific augmentation of the MRI water signal in the ER-positive versus ER-negative xenografts, confirming EPTA-Gd specific interaction with ER. In contrast, TPTA-Gd did not show increased enhancement in ER-positive tumors and did not appear to interact in vivo with the tumors’ ER. However, TPTA-Gd was found to interact strongly with muscle tissue, enhancing muscle signal intensity in a mechanism independent of the presence of ER. The specificity of EPTA-Gd interaction with ER in vivo was further verified by acute and chronic competition with tamoxifen. The chronic tamoxifen treatment also revealed that this drug increases the microvascular permeability of breast cancer xenograft in an ER independent manner. In conclusion, EPTA-Gd has been shown to serve as an efficient molecular imaging probe for specific assessment of breast cancer ER in vivo.